(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The primary objective of this review is to conduct a comprehensive study on the topical delivery of luliconazole using the microsponge method to enhance the drug’s efficacy. The study encompasses a detailed examination of gels, various types of gels, different layers of the skin dermis, and the mechanism of action of the drug on infected areas. Additionally, it explores fungal infections in depth. Microsponges containing Luliconazole (API) with varying proportions of drug polymers were efficiently prepared using the quasi-emulsion solvent diffusion method. This approach aims to minimize side effects, reduce skin secretions, and enhance therapeutic efficacy at lower doses, thereby optimizing the drug delivery system. The quasi-emulsion solvent diffusion method utilized different polymers such as HPMC, Polyvinyl Ethyl cellulose, and others to achieve these objectives.